2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33506
|View full text |Cite
|
Sign up to set email alerts
|

Using LEGO Mindstorms and MATLAB in Curriculum Design of Active Learning Activities for a First-year Engineering Computing Course

Abstract: She is an instructor in the introductory engineering courses as well. The BSEN program at MacEwan has grown from forty students since in started almost fifteen years ago, to the current 216 students. The majority of the students in the program transfer to second year engineering at the University of Alberta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We rely upon MATLAB because it is user-friendly, has intuitive package management, and can be easily interfaced with the Lego Mindstorm EV3 robot. Our literature review only found a single source similar to our work utilizing both the Lego Mindstorm EV3 robot in combination with MATLAB software as a way to introduce students to programming basics [12]. In contrast, we present the fundamentals of programming prior to introducing the robots, allowing students time to grasp concepts before complicating codes with unfamiliar sensors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We rely upon MATLAB because it is user-friendly, has intuitive package management, and can be easily interfaced with the Lego Mindstorm EV3 robot. Our literature review only found a single source similar to our work utilizing both the Lego Mindstorm EV3 robot in combination with MATLAB software as a way to introduce students to programming basics [12]. In contrast, we present the fundamentals of programming prior to introducing the robots, allowing students time to grasp concepts before complicating codes with unfamiliar sensors.…”
Section: Literature Reviewmentioning
confidence: 99%